A GIS based dataset to assess the influence of countryside planning policies on landscape change in Bedfordshire - Peccol, Elisabetta (Cranfield University, 1994)
A GIS database for a study area (96 Km^) within the county of Bedfordshire (southern England) was established to provide statistical and mapped information on the distribution, extent and change through time of land-cover and landscape features between 1968, 1981 and 1991. A major aim of the project was to investigate the character of the countryside designation zones operating in Bedfordshire in terms of detailed local landscape. The effectiveness of the policies for the countryside was assessed in terms of the landscape changes monitored in each area. To this purpose a census of landscape features was carried out by means of aerial photographic interpretation and the differences between the three dates were measured. The classification scheme included 19 land-cover types (area features), 6 linear features and 6 point features. A Digital Terrain Model was used to analyse the land-fonn of the study area and its influence on the distribution of land-cover types. The countryside designation zones were digitised from the Local Plans and processed with the land-cover maps. The results of the project are represented by maps, tables and charts of landscape features for each date and their changes between each date, in the study area and in the countryside designation zones. The study area is shown to be intensively managed since agro-pastoral and developed land cover most of its area. Countryside designation zones showed a strong agro-pastoral character, except for the Sites of Special Scientific Interest and the National Nature Reserve. Generally, over the two decades analysed, both the study area and the countryside designation zones suffered changes in landscape features.